APLIKASI SEDUHAN BUNGA ROSELLA (Hibiscus sabdariffa) SEBAGAI ASIDULAN PADA ROTI MANIS BERBASIS TEPUNG GAPLEK - Ananingsih, Victoria Kristina; Ardanareswari, Katharina; Yuliarto, Theo Rony (Jurnal Teknologi Pangan dan Gizi, 2018)
Gaplek flour is processed from cassava (Manihot utilissima), which is dried and milled. Its application as wheat flour substitute in sweet bread brings some minor qualities in final bread volume. In this case, addition of leavening agent such as baking soda and acidulant is crucial. Rosella (Hisbiscus sabdariffa) flower infusion is known with its acidic taste, however, its application as natural acidulant has never been explored before. The purpose of this research is to explore the effect of rosella flower infusion as natural acidulant towards physicochemical characteristic of gaplek flour-based sweet bread. In this research, wheat flour was substituted by gaplek flour in amount of 10%, 20% and 30%.Rosella flower infusion was added as 25%, 50% and 75%of water portion added. Physicochemical assays of the resulting sweet bread were done, including the assay of bread volume, average of pore’s diameter, hardness, and water content. The result shows that sweet bread with higher concentration of gaplek flour substitution exhibit lower volume with higher hardness. Addition of rosella flower infusion results in improvement of bread volume and hardness. In sweet bread with 30% gaplek flour substitution, addition of 75% acidulant increase the volume up to 45% higher and decrease the hardness up to 18% lower than the sample without acidulant. The volume of 30% gaplek, 75% acidulant sample is even higher compared to flour control sample without acidulant. It is concluded that addition of acidulant based on rosella flower infusion improves characteristics of gaplek flour-based sweet bread.